Optimal methods of wastewater treatment in deposits - Bokiyeva, Sh.K.; O’ktamov, J.J. (Science and Education, 2024)
This article highlights modern methods of wastewater treatment in the oil and gas industry, effectively removed components are oils. The treatment of these wastewater requires engineering developments that can provide comprehensive, reliable, efficient and optimized solutions.